2009
DOI: 10.1017/s1743921310002693
|View full text |Cite
|
Sign up to set email alerts
|

The current status on the UV upturn

Abstract: Abstract. The UV upturn phenomenon found in giant elliptical galaxies through space observations has been a mystery. Recent GALEX observations have revealed new facts. The most notable is the rarity of UV upturn galaxies. Unlike previous beliefs, UV upturn is found only in less than 10 percent of giant ellitpical galaxies. Another notable finding is that the UV flux has been increasing for the last couple of billion years. This is consistent with the theoretical predictions that suggest hot horizontal branch s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…For this thesis, I made use of the MIS sample, which provides the best compromise in terms of sky coverage and image depth (see Table 2.3), a similar approach taken by previous UV upturn studies making use of GALEX data (for instance, Ree et al 2007 made use of both MIS and DIS observations to create a sample of brightest cluster galaxies, BCGs). A detailed discussion on the use of the different GALEX surveys to study the UV upturn phenomenon can be found in Yi (2008).…”
Section: Galex Gr6/plus7mentioning
confidence: 99%
“…For this thesis, I made use of the MIS sample, which provides the best compromise in terms of sky coverage and image depth (see Table 2.3), a similar approach taken by previous UV upturn studies making use of GALEX data (for instance, Ree et al 2007 made use of both MIS and DIS observations to create a sample of brightest cluster galaxies, BCGs). A detailed discussion on the use of the different GALEX surveys to study the UV upturn phenomenon can be found in Yi (2008).…”
Section: Galex Gr6/plus7mentioning
confidence: 99%
“…The Ultraviolet Upturn or Excess is an unexpected rise in flux in the spectral energy distributions of early-type galaxies shortwards of 2500Å. It appears to be a nearly ubiquitous property of spheroids and bulge-dominated galaxies (see, e.g., Yi 2008Yi , 2010 for a recent review) although their generally old, metal-rich and quiescent stellar populations (e.g., Thomas et al 2005Thomas et al , 2010 should contain no sources capable of providing significant flux below the 4000Å break. While many candidates have been proposed, the source population is generally agreed to consist of hot horizontal branch (HB) stars (Greggio & Renzini 1990;Brown et al 1998a) and it now appears most likely that this population is heliumrich and formed in situ at high redshift (Ali et al 2018a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…In spiral and irregular galaxies, flux emitted in the UV acts as an excellent measure of the current star formation rate (Gil de Paz et al 2007). In the case of (mostly quiescent) early-type galaxies, the flux at wavelengths shorter than 1800Å (FUV) is believed to be produced by hot, low mass Horizontal Branch (HB) stars, although the mechanism with which an old population can develop hot stars is still hotly debated (see Yi 2008). For the non-quiescent, low redshift elliptical galaxies, analysis of UV wavelengths longer than 1800Å (NUV) is a useful indicator of residual star formation (Pipino et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is motivated by globular cluster observations containing peculiar features in the colour magnitude diagram that can only be explained by the presence of super-helium-rich subpopulations (D' Antona & Caloi 2004;Norris 2004;D'Antona et al 2005; Lee et al 2005;Piotto et al 2005). These populations could be a major source of FUV flux in quiescent el-liptical galaxies, although studies suggest that the deduced value of the helium abundance is too small to be influential on galactic scales (Lee et al 2005;Yi 2008). However, in the centres of clusters, an extra source of helium could come from sedimentation processes (Peng & Nagai 2009).…”
Section: Introductionmentioning
confidence: 99%